Coordinated regulation of gene expression and microRNA changes in adipose tissue and circulating extracellular vesicles in response to pioglitazone treatment in humans with type 2 diabetes - Nunez Lopez, Yury O.; Casu, Anna; Kovacova, Zuzana; Petrilli, Alejandra M.; Sideleva, Olga; Tharp, William G.; Pratley, Richard E. (Frontiers in Endocrinology, 2022)
Pioglitazone, a PPARγ agonist, is used to treat type 2 diabetes (T2D). PPARγ is highly expressed in adipose tissue (AT), however the effects of pioglitazone to improve insulin sensitivity are also evident in other tissues and PPARγ agonism has been shown to alter cancer derived extracellular vesicle (EV)-miRNAs. We hypothesized that pioglitazone modifies the cargo of circulating AT-derived EVs to alter interorgan crosstalk in people with diabetes. We tested our hypothesis in a 3-month trial in which 24 subjects with T2D were randomized to treatment with either pioglitazone 45 mg/day or placebo (NCT00656864). Levels of 42 adipocyte-derived EV-miRNAs were measured in plasma EVs using low density TaqMan arrays. Levels of differentially expressed EV miRNAs and their most relevant target genes were also measure in adipose tissue from the same participants, using individual TaqMan assays. Levels of 5 miRNAs (i.e., miR-7-5p, miR-20a-5p, miR-92a-3p, miR-195-5p, and miR-374b-5p) were significantly downregulated in EVs in response to pioglitazone treatment relative to placebo. The opposite occurred for miR-195-5p in subcutaneous AT. Changes in miRNA expression in EVs and AT correlated with changes in suppression of lipolysis and improved insulin sensitivity, among others. DICER was downregulated and exosomal miRNA sorting-related genes YBX1 and hnRNPA2B1 displayed a downregulation trend in AT. Furthermore, analysis of EV-miRNA targeted genes identified a network of transcripts that changed in a coordinated manner in AT. Collectively, our results suggest that some beneficial pharmacologic effects of pioglitazone are mediated by adipose-specific miRNA regulation and exosomal/EV trafficking.